2018
DOI: 10.3389/fendo.2018.00300
|View full text |Cite
|
Sign up to set email alerts
|

The Big Entity of New RNA World: Long Non-Coding RNAs in Microvascular Complications of Diabetes

Abstract: A major part of the genome is known to be transcribed into non-protein coding RNAs (ncRNAs), such as microRNA and long non-coding RNA (lncRNA). The importance of ncRNAs is being increasingly recognized in physiological and pathological processes. lncRNAs are a novel class of ncRNAs that do not code for proteins and are important regulators of gene expression. In the past, these molecules were thought to be transcriptional “noise” with low levels of evolutionary conservation. However, recent studies provide str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 85 publications
(88 reference statements)
1
23
0
Order By: Relevance
“…Finally, long non-coding RNA (lncRNAs) is a novel class of RNA that does not code for proteins and are important regulators of gene expression. Recent studies have found that diabetes correlates with an aberrant expression of these molecules ( Raut and Khullar, 2018 ). Briefly, lncRNA-myocardial infarction-associated transcript (MIAT) expression is upregulated in models of diabetic cardiomyopathy and when knocked down, there are improvements in cardiac function and a decrease in cardiomyocyte apoptosis ( Zhang et al, 2016 ; Zhou et al, 2017 ).…”
Section: New Potential Targets For Future Therapiesmentioning
confidence: 99%
“…Finally, long non-coding RNA (lncRNAs) is a novel class of RNA that does not code for proteins and are important regulators of gene expression. Recent studies have found that diabetes correlates with an aberrant expression of these molecules ( Raut and Khullar, 2018 ). Briefly, lncRNA-myocardial infarction-associated transcript (MIAT) expression is upregulated in models of diabetic cardiomyopathy and when knocked down, there are improvements in cardiac function and a decrease in cardiomyocyte apoptosis ( Zhang et al, 2016 ; Zhou et al, 2017 ).…”
Section: New Potential Targets For Future Therapiesmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNA), a newly discovered type of RNA transcripts with more than 200 nucleotides, were proved to regulate gene expression and progression of complex human diseases . As lncRNA lacks protein‐coding potential, it was previously defined to be transcriptional “noise.” However, more and more data show that lncRNA possess critical functions in various tissues and cell types …”
Section: Introductionmentioning
confidence: 99%
“…Among other lncRNAs which act as regulators of diabetic tubular injury in DKD 39 , 40 , 41 , the expression of lncRNA MIAT was reduced and negatively correlated with serum creatinine and blood urea nitrogen levels 24 , 42 . It is assumed that lncRNAs could be potential regulators of high glucose-induced renal tubular injury.…”
Section: Discussionmentioning
confidence: 99%